(untitled) (Research, Society and Development, 2024)
The oral cavity, besides showing variations on its normality standard, it also might express clinical signs of local lesions or clinical signs of systemic diseases which require a specific therapeutic approach. Therefore, the early recognition of oral lesions represents a clinical challenge in Stomatology. Thus, this research aimed to characterize in a qualitative and quantitative way the lesions found in the oral cavity of users of the bucal diagnosis, in the secondary health care, in a pernambucano county. This research is a cross-sectional study carried out between October of 2022 and March of 2023, with patients who required specialized care in bucal diagnosis. Were diagnosed 22 lesions in the sample which was comprised by 45 individuals. The lesions were devided in two groups for a better comprehension of the presentations. In the first group, the lesions with a higher prevalence were fibrous hyperplasia 37% (n=10), followed by denture stomatitis 15% (n=4). In the second group, the lesions with a higher prevalence were leukoplakia 20% (n=4) followed by vacular lesions with the same percentagem. It was concluded that life habits and sociodemographic factors were directly related to some lesions present in the oral cavity. The presence of lesions in the oral cavity, as well as the high tobacco load, of the smoker individuals were related to lesions found in their oral cavity in the physical exam.